Conversion method of specific absorption rate to absorbed power density for the assessment of human exposure to radio frequency electromagnetic fields from wireless devices in close proximity to the head and body. Frequency range of 6 GHz to 10 GHz. (30th November 2022) - British Standards Institution,
No abstract available